Making sweet potato chips and flour - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
This leaflet describes how to make money from sweet potatoes by making and selling high-quality sweet potato chips and flour.